2022
DOI: 10.2174/1389557522666220404090429
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Natural Polyphenols as Antiparasitic Agents and their Biochemical Targets

Abstract: Background: Leishmaniasis and trypanosomiasis are diseases that affect public health worldwide due to their high incidence, morbidity, and mortality. Available treatments are costly, prolonged, and toxic, not to mention the problem of parasite resistance. The development of alternative treatments is justified and polyphenols show promising activity. Objective: The main aim of this mini-review was to analyze the most promising phenolic compounds with reported antileishmanial and antitrypanosomal activity as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…They include flavonoids and phenolics and well known for their health benefits and biological properties such as antioxidant, anti-inflammatory, antimicrobial, anticancer and antiparasitic [ [66] , [67] , [68] , [69] , [70] ]. Many studies have reported polyphenols as antitrypanosomal agents [ [71] , [72] , [73] , [74] , [75] , [76] ]. Tannins are phytochemicals that have been demonstrated to possess anti-inflammatory, antimicrobial, antioxidant, immunomodulatory, and antiparasitic properties [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…They include flavonoids and phenolics and well known for their health benefits and biological properties such as antioxidant, anti-inflammatory, antimicrobial, anticancer and antiparasitic [ [66] , [67] , [68] , [69] , [70] ]. Many studies have reported polyphenols as antitrypanosomal agents [ [71] , [72] , [73] , [74] , [75] , [76] ]. Tannins are phytochemicals that have been demonstrated to possess anti-inflammatory, antimicrobial, antioxidant, immunomodulatory, and antiparasitic properties [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The aim is to demonstrate the presence of events related to programmed or apoptotic cell death in the parasites, avoiding compounds that produce necrotic cell death, as this would produce an undesirable inflammatory response in the hosts [27]. Some events have been previously relative to programmed cell death, among these, the accumulation of reactive oxygen species (ROS), alterations in mitochondrial membrane potential, exposure to phosphatidylserine, decrease in cellular ATP levels, disruption in the plasma membrane, DNA fragmentation, and chromatin condensation [27][28][29][30]. In the present work, some of these events were studied to elucidate the type of cell death produced by flucofuron in parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a continuous effort to discover new drugs to improve the treatment of these parasitosis. Plants possess numerous biologically active chemical compounds, including flavonoids, anthocyanidins, coumarins, and terpenes, which exhibit antiparasitic activity (Da Silva et al., 2018; Raimundo et al., 2022; Soto‐Sánchez, 2022). Terpenes are a very diverse group of molecules with very different structures and functions, of regular size, consisting of complete isoprene units (C 5 H 8 ).…”
Section: Introductionmentioning
confidence: 99%